FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PEKERJA DI PT SINARINDO MANDIRI PERKASA TAHUN 2023 - Nur Azizah Wafiqoh Robbani (2023)
Fatigue can affect the effectiveness, productivity, and safety of workers due to decreased worker alertness which can lead to errors, increased incidents, and injuries. The purpose of the study is to analyze the factors related to work fatigue in workers of PT Sinarindo Mandiri Perkasa. This research uses analytical research method with cross-sectional approach. The sampling technique used was total sampling with a minimum sample size of 114 respondents. The results showed that the percentage experienced from the univariate analysis showed that as many as 30 respondents (26.1%) experienced mild fatigue, 82 respondents (71.3%) experienced moderate fatigue, and 3 respondents (2.6%) experienced severe fatigue. The Chi Square test showed that age (0.023) and work duration (0.041) show a relationship during the working period, nutritional status, smoking habit, mental workload, physical workload, noise, lighting, and work climate showed no relationship. The recommendations are maximizing rest time, managing work duration so that it does not exceed the specified time, and conducting health checks, especially for workers at risk of experiencing work fatigue.